THE TAX COMPLIANCE RISK FOR BANK PAYMENT TRANSACTIONS IN THE TAX ADMINISTRATION CONTEXT IN VIETNAM - Vo, Dung Tien (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2019)
The article provides the reference on tax compliance risk for bank transactions payments by businesses in the context of developing countries such as Vietnam, as tax departments are gradually modernizing the tax administration, the use of taxpayer data between tax department and banks are not good. The review of the materials examines the issues involved in the field of tax compliance risk management and to identify gaps in the study of a tax compliance risk.